Technical-economic evaluation of application scenarios of an organic rankine cycle (ORC) as a solution to the cogeneration deficit in a sugar plant - Chumpitaz Ayala, German R. (2024)
There is currently a cogeneration deficit at a sugar plant near Nepeña, Ancash, Peru, where the exhaust steam from the mill area is approximately 235◦C. The steam should be at a temperature close to 120◦C, therefore, the heat is dissipated without being recovered. The waste heat available in the plant is mainly exhaust gases and mill area exhaust steam, so the installation of an Organic Rankine Cycle (ORC) is proposed as a solution for the use of waste heat, with the objective of optimizing cogeneration in the plant. Three systems are proposed: ORC with exhaust gas system, ORC with unified system and ORC with total unified system, so the thermoeconomic analysis in this article is made based on a Series Heat Exchangers ORC (SHEORC). For this purpose, six scenarios will be analyzed in which the electrification of the mills and the direct sale of energy to the power grid will be proposed. The results obtained are: the increase in the overall efficiency of the plant is between 6.58 and 14.67%, the annual saving in CO2 emissions between 914.65 and 2631.77 Ton CO2/year, the exergy efficiency between 60.93 and 65.4% and the LEC (Levelized Electrical Cost) between 35.73 and 58.05 $/MW.h.